Local Perception on Effect of Land Degradation in the Blue Nile River Headwaters - Alelgn Ewuntu Temesgen (European Journal of Geography)
Poor land-use practices have threatened the livelihood of rural people in Ethiopia. This study assessed the local perception of the impact of land degradation on rural livelihood in the Blue Nile river headwaters, North Gojjam sub-basin. To achieve this objective, questionnaires were administered for 414 sample households and series of focus group discussions and detailed interviews were held with participants. Descriptive statistics were used to analyze quantitative data while qualitative data were buildup using narration and simple description approaches. The finding showed that all local farmers perceived that land degradation was the main local ecological problem since 2008 in the form of soil erosion, soil nutrient depletion; soil acidity and soil biodiversity loss. Most of them (62.54%) perceived as land degradation severity was high and increasing through time, primarily on cereal crop land. Population growth, using animal dung and crop residue for domestic cooking and heating energy, free grazing, using crop residue for construction, absence of fallowing, poor farming, steep slope, and using inappropriate SWC technologies are the main causes of land degradation in the study area. Most local farmers observed as land degradation has decreased crop and livestock productivity, firewood, and surface water resources accessibility. These resulted in the decline in households’ food security and net income over the last 10 years. The finding showed that farmers used traditional ditche, hillside terrace, soil bund, stone bund, check dam, and waterway to reduce land degradation.